Rediscovery of the enigmatic Scutellaria xylorrhiza (Scutellarioideae; Lamiaceae)—a rare endemic species from Iran - Salmaki, Yasaman; Müller, Jochen (Phytotaxa, 2019)
After more than 100 years since the first discovery, Scutellaria xylorrhiza, a critically endangered species listed in the Red List of Iranian plants had been presumed to be extinct. We rediscovered recently a population of this species in Sofeh Mountain South of Isfahan. Here, we perform the taxonomic history, phylogenetic placement and conservation status of this endemic species, and compare our findings with the description provided in the protologue and other references. Besides the updated description, notes on typification and new photographs of this species are presented. In addition, we compare S. xylorrhiza with other related Scutellaria species occurring in Iran and neighboring regions using molecular sequence data from the nuclear ribosomal DNA (Internal Transcribed Spacer). Our morphological and sequence analyses show that S. xylorrhiza is close to S. ariana.